Motion Decay of a Floating Object - Bengtsson, Mikael; Delvret, Max (My University, 2021)
In today's growing demand for green energy the utilisation of ocean waves as an energy source is an attractive possibility. Computational fluid dynamics is an efficient and cheap way to test different design and environment conditions. Two different software are evaluated in this report in order to see possibilities and limitations of the different software. The software used in this project are FINE™/Marine and OpenFOAM. Guidelines are then presented of how to set up an accurate and efficient simulation of a wave energy converter. In this project three different meshing methods were tested, to see how efficient and accurate they are. The different meshing techniques were overset, sliding, and a deforming mesh technique, the different methods also required different case setups which is presented in this report. A 0.15 meter radius sphere is dropped from 0.15 meter above the water surface and its motion is investigated for six seconds. The result for the different meshing techniques is then validated with experimental data. The overset mesh technique was determined to be the most accurate and stable method but it was the most computational heavy method. The overset mesh technique was tested with a k--!--SST model to determine the effects of the turbulence. It was discovered that the turbulence was not significantly affecting the heave motion of the sphere. The simulation case was then scaled up and a drop for a ve meter radius sphere is simulated with its center of mass five meter above the resting water surface. This was done in order to show that the simulation method could be scaled up. The overset mesh technique was used for this case since it was determined to be the most accurate and stable method. The heave motion of the sphere was investigated for 40 seconds and the result was found to agree with numerical data from previous studies. A numerical wave tank case with an overset mesh was setup in OpenFOAM in order to show the potential energy production of a wave energy converter. However further studies is needed for incoming waves since there doesn't exist any experimental data to validate with.
Keywords: OpenFOAM; FINE™/Marine; OEC; NWT; VOF; Overset mesh technique; Sliding mesh technique; Deforming mesh technique; RANS